Fitness consultations in routine care of patients with type 2 diabetes in general practice: an 18-month non-randomised intervention study - Lohmann, Henning (BioMed Central, 2010)
BACKGROUND: Increasing physical activity is a cornerstone in the treatment of type 2 diabetes and in general practice it is a challenge to achieve long-term adherence to this life style change. The aim of this study was to investigate in a non-randomised design whether the introduction of motivational interviewing combined with fitness tests in the type 2 diabetes care programme was followed by a change in cardio-respiratory fitness expressed by VO(2max), muscle strength of upper and lower extremities, haemoglobin A(1c )(HbA(1c)) and HDL-cholesterol. METHODS: Uncontrolled 18-month intervention study with follow-up and effect assessment every 3 months in a primary care unit in Denmark with six general practitioners (GPs). Of 354 eligible patients with type 2 diabetes, 127 (35.9%) were included. Maximum work capacity was tested on a cycle ergometer and converted to VO(2max). Muscle strength was measured with an arm curl test and a chair stand test. The results were used in a subsequent motivational interview conducted by one of the GPs. Patients were encouraged to engage in lifestyle exercise and simple home-based self-managed exercise programmes. Data were analysed with mixed models. RESULTS: At end of study, 102 (80.3%) participants remained in the intervention. Over 18 months, VO(2max )increased 2.5% (p = 0.032) while increases of 33.2% (p < 0.001) and 34.1% (p < 0.001) were registered for the arm curl test and chair stand test, respectively. HDL-cholesterol increased 8.6% (p < 0.001), but HbA(1c )remained unchanged (p = 0.57) on a low level (6.8%). Patients without cardiovascular disease or pain from function limitation increased their VO(2max )by 5.2% (p < 0.0001) and 7.9% (p = 0.0008), respectively. CONCLUSIONS: In this 18-month study, participants who had repeated fitness consultations, including physical testing and motivational interviewing to improve physical activity, improved VO(2max), muscle strength, and lipid profile. Our results indicate that physical testing combined with motivational interviewing is feasible in a primary health care setting. Here, a fitness consultation tailored to the individual patient, his/her comorbidities and conditions in the local area can be incorporated into the diabetes programme to improve patients' muscle strength and cardio-respiratory fitness.